Effect of endoscopic sinus surgery on clinical outcomes in DeltaF508 cystic fibrosis patients. (13th March 2021) - Dadgostar, Anali; Nassiri, Sepehr; Quon, Bradley S.; Manji, Jamil; Alsalihi, Salahuddin; Javer, Amin
Abstract: Objectives: Chronic rhinosinusitis (CRS) is prevalent in the Cystic Fibrosis (CF) population. CRS exacerbations in CF are thought to contribute to pulmonary exacerbations. Literature regarding the impact of endoscopic sinus surgery (ESS) is inconclusive. This study examines rates of lung function decline and pulmonary exacerbation in CF patients who have undergone ESS. Design: Retrospective review of medical records. Setting: Academic Hospital. Participants: 40 adult CF patients. Main outcome measures: Rate of lung function decline (% predicted Forced Expiratory Volume in 1 second [ppFEV1 ]), number of pulmonary exacerbations (IV/oral antibiotic therapy ± hospital admission) and total number days hospitalised 2‐year postoperatively was collected. CRS patients undergoing ESS were matched to those without ESS by gender, age, and F508del genotype. Results: Forty patients (mean age 37.4, 60% male) were reviewed. No significant difference was found between the surgical group and controls in baseline ppFEV1 (72.5% vs. 72.7%, P  = .98), 2‐year preoperative number of pulmonary exacerbations (3.05 vs. 1.65, P  = .10), or Lund‐Mackay scores (12.25 vs. 11.55, P  = .71). No significant difference was found in 1‐year (70.5% vs. 72.8%, P  = .84) or 2‐year (70.4% vs. 72.6% P  = .80) postoperative ppFEV1 and 2‐year postoperative pulmonary exacerbations (1.7 vs. 1.45, P  = .87). A significant increase was identified in total number days hospitalised postoperatively (4.85, P  = .02). In the surgical group, no significant difference was identified between preoperative and postoperative ppFEV1, 1 year (−2.51%, P  = .32) and 2 years after ESS (−3.10%, P  = .51), postoperative rate of pulmonary exacerbations (−1.28, P  = .11), or in total number days hospitalised (3.74, P  = .14). Conclusions: In this study, ESS does not appear to significantly improve ppFEV1 or decrease the number of pulmonary exacerbations postoperatively.